Gold in Peru: Present status and future challenge - Acosta Ale, Jorge Gilberto (2015)
Total reported gold resources in Peru is about 192 Moz. Gold production in Peru was 4.9 Moz in 2013, which was ranked first in Latin America and sixth in the world. Historic cumulative gold production in Peru is 118 Moz, and production from main gold belts including Miocene epithermal belt, Carboniferous-Permian orogenic gold belt and Upper Cretaceous intrusion-related gold belt corresponds to 84%. Most of production areas are located in Northern part of Peru, which corresponds to 63.5% of the total domestic production. Annual production onces in Yanacocha mine and Alto Chicama were 1 Moz and 0.606 Moz in 2013, which were ranked first and second in Peru, respectively. Gold production in Peru is expected to be 6.5 Moz in 2017. To accomplish the expected production, ongoing 14 projects should be developed to the production stage in three years.